Non-alcoholic fatty liver disease in general paediatric population - associated factors and screening by Ultrasonography - L., Mounica; T., Nair Bindu; Piyush, Dhagat (International Journal of Contemporary Pediatrics, 2019)
Background: Ultrasonography(USG) is an easily available and non-invasive method for screening the general paediatric population for prevalence of non-alcoholic fatty liver disease (NAFLD). Methods: This was a cross-sectional descriptive study conducted in the Paediatric Out Patient Department on 100 randomly selected children of school going age group (5-15 years). A detailed history regarding diet and lifestyle, anthropometric measurements of the children like height, weight , BMI and waist – hip ratio and blood pressure was correlated with USG of general paediatric population. Results: There were 4 cases of NAFLD of which one case was of normal weight. The study shows that the mean weight of normal population was 33.36 kgs. while the mean weight of children with fatty liver was 56.38 kgs. The mean value of systolic and diastolic blood pressure in normal population is 98.46 mmHg and 57.48 mmHg respectively while in that of children with NAFLD, it was 119.00 mmHg and 78.50 mmHg respectively. Among the dietary factors, increased intake of non-veg food, fast food, soft drinks and decreased intake of eggs and fish food is seen in children with NAFLD. Children with decreased physical activity also showed to have increased NAFLD. Conclusions: As NAFLD is seen even in children with normal weight, all children of general pediatric population can be screened for NAFLD by an easily available and non-invasive method like USG for an early intervention to prevent morbidity associated with NAFLD.